CHALLENGES IN EFL LEARNING: A STUDY OF FIRST-YEAR STUDENTS AT PRIVATE UNIVERSITIES IN BANGLADESH - Islam, Zahirul; Ann-Noor, Zebin Tasnim (Universitas Negeri Makassar, 2025)
This research investigates the key challenges encountered by first-year students studying English as a Foreign Language (EFL) at two private universities in Bangladesh, using firsthand feedback provided by the learners. Adopting a mixed-methods approach that incorporates both qualitative and quantitative techniques, the study uncovers meaningful insights into the academic and linguistic difficulties the students experience. Key challenges found are that students are reluctant to speak, have trouble with pronunciation and understanding, lack enough vocabulary, have writing difficulties and face issues due to cultural differences. These issues reveal a complex relationship among language proficiency, psychological factors, and cultural context. Students also highlighted the essential support teachers can hand with a view to overcoming these barriers, emphasizing the need for more active guidance and assistance. Based on these findings, the study recommends regular assessment of teaching strategies and the implementation of focused support initiatives. In addition, it encourages collaborative efforts among students, instructors, and academic institutions to foster a more effective and inclusive EFL learning environment. The results offer valuable insights for enhancing language education strategies tailored to first-year learners at private universities in Bangladesh.